STRUKTUR SOSIAL EKONOMI KELUARGA, KAPITAL SOSIAL, DAN PRESTASI BELAJAR SISWA DI SMA LABSCHOOL JAKARTA, RAWAMANGUN JAKARTA TIMUR - Marsono, Marsono; Zaka Lawang, Robert Markus (Jurnal Insani, 2018)
The family has a role and function in producing social capital. Changes in family structure will eliminate social capital, this is due to the absence of parents who work outside the home. If the human capital of the parents is spent mostly in the workplace and elsewhere outside the home, the family is unable to play a role in producing the social capital that the child needs in achieving its learning achievements. This study aims to examine the influence of socio-economic structure of family and social capital with the children’s learning achievement.The analytical tool used is logistic regression, because the dependent variable (Y) in this study is binary consisting of two (2) categories of 0 and 1. Result of research based on result of logistic analysis show that simultaneously show variable of social economic structure of family and social capital can explain variable of achievement learn equal to 30,6% while 69,4% other factor explain variable of learning achievement. The result of odds ratio test shows that students who have high socio-economic structure of family have opportunity to get high learning achievement equal to 1,942-16,981 times compare with student having low socioeconomic family structure. Students who have high family social capital have the opportunity to obtain high learning achievement of 2,239-38,846 times compared to students who have low family social capital.